PENDEKATAN BALANCE SCORECARD UNTUK PENGUKURAN KINERJA PADA DINAS KESEHATAN KABUPATEN BONDOWOSO - Setyawan, Donie (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
Public sector performance of the government institutions in Bondowoso Regency is measured from organizational ability in realizing budget absorption at the end of the budget year. However, referring merely to the financial aspect cannot provide objective and comprehensive overview of the overall organizational performance. Therefore, an objective and comprehensive measurement is needed, both from the financial (quantitative) and non financial aspects (qualitative). This research aims to analyze the implementation of balanced scorecard concept in describing the overall performance achievement and determining organizational policies and strategies in the Health Department of Bondowoso Regency. This is a qualitative research applying case study approach. Data were collected from questionnaires distribution, interview, and literatures study. This research focuses on 4 perspectives in describing organizational service quality, i.e., financial perspective, customer perspective, internal business process perspective, and growth & learning perspective. Results show that: (1) the financial performance quality is economically adequate, quite effective and efficient, (2) from the customer perspective, the performance quality is satisfactory, (3) the quality performance of internal business process is satisfactory, and (4) from the learning and growth perspective, the performance quality is satisfactory. Keywords: Performance, Quality, Balanced Scorecard.